(Bi0.5Na0.5)TiO3 ferroelectric ceramics: Achieving high depolarization temperature and improved piezoelectric properties. Issue 15 (December 2020) - Han, Jihui; Yin, Jie; Wu, Jiagang
Abstract: (Bi1/2 Na1/2 )TiO3 -based materials have received much attention due to large electro-strain and high piezoelectric constant ( d 33 ), but the tough issue is that the existence of inherent depolarization temperature ( T d ) limits the temperature stability and application temperature range. Previously, reports about the formation of BNT/oxide (i.e., ZnO, Al2 O3 ) composites thought that T d can be deferred to a higher temperature and then thermal depolarization improves. However, the deferred T d of BNT/oxide composites is limited, accompanied by a low d 33 . Here, we design the {[Bi0.5 (Na0.8 K0.2 )0.5 ]1- x Pb x }TiO3 ceramics, leading to a big shift of T d from 77 ℃ to 390 ℃. Large d 33 (140 pC/N) and high T d (∼263 ℃) can be simultaneously achieved for the sample with Pb=0.05, and T d could be further deferred higher (390 ℃) for Pb=0.20. The off-centre displacement of Pb induced by Pb-O hybridization in the PbO12 polyhedron and ferroelectric order stabilized by the addition of Pb can provide the driving force to strengthen the ferroelectric order, and then promote the thermal stability.